Associations between acrylamide and brain-derived neurotrophic factor levels in children in a European biomonitoring study - Elisabeth Strømdahl; Oddvar Myhre; Birgitte Lindeman; Anne Lise Brantsæter; Andrea Rodríguez-Carrillo; Mariana F. Fernández; Fabio Barbone; Valentina Rosolen; Alicia Olivas-Martinez; Greet Schoeters; Eva Govarts; Cathrine Thomsen; et al. (Environmental Research, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

Examination of DNAm PhenoAge as an epigenetic biomarker for perioperative risk in adult spinal deformity surgeries - Michael P. Kelly; Jeffrey Hills; Justin S. Smith; Lawrence G. Lenke; Han Jo Kim; Shay Bess; Breton Line; Virginie Lafage; Renaud Lafage; Eric Klineberg; Ferran Pellise; Khaled Kebaish; et al. (GeroScience, 2026)

Per- and polyfluoroalkyl substances (PFAS) and miscarriage: The Norwegian Mother, Father and Child Cohort study - Thea Grindstad; Maria C. Magnus; Alessandro Di Nallo; Cecilia Høst Ramlau-Hansen; Zeyan Liew; Hans Ivar Hanevik; Line S. Haug; Gro D. Andersen; Tormod Rogne; Eleni Papadopoulou; Per Magnus; Siri E. Håberg; et al. (Environmental Research, 2026)

Symbiodiniaceae shifts over the last decade on the hottest coral reefs on Earth - Anna Fiesinger; Rachel Alderdice; Luigi Colin; Hannah Manns; Gabriela Perna; Kathryn H. Stankiewicz; Jacob J. Valenzuela; Line K. Bay; Daniel J. Barshis; Nitin S. Baliga; Iliana B. Baums; John A. Burt; et al. (Coral Reefs, 2025)
Corals in the Persian/Arabian Gulf (PAG) are resilient to various stressors, whose levels exceed those of coral reefs globally. These corals thereby offer insight into mechanisms underlying thermal resilience, e.g., regarding the role of endosymbiotic microalgae in the family Symbiodiniaceae. Previous studies have identified the thermotolerant species Cladocopium thermophilum as broadly associated with corals in the southern PAG. However, algal-host specificity at the within-species level and the temporal stability of these associations are not well understood. Here we sampled two dominant stony corals ( Porites harrisoni , n = 119 and Platygyra daedalea , n = 79) at three sites in the southern PAG and the neighboring Gulf of Oman (GO) to explore algal symbiont assemblage and specificity, whereby a prior dataset provided the opportunity to assess symbiont community stability in P. daedalea across a decadal time frame. Using high-throughput ITS2 marker gene sequencing and the SymPortal framework, we identified distinct, largely non-overlapping ITS2 type profiles of C. thermophilum as the dominant symbiotic partners in P. harrisoni and P. daedalea in the southern PAG, highlighting high host fidelity at the subspecies level. Despite this, we observed notable changes in C. thermophilum genotype diversity and an overall decrease over the course of a decade. By comparison, algal symbiont diversity in the neighboring GO corals increased, with formerly prevalent ITS2 type profiles being replaced by novel genotypes. Decadal data on P. daedalea suggest a shift in algal symbiont assemblage signified by the decline of formerly dominant algal type profiles and the emergence of novel genotypes. It is currently unknown whether the respective coral colonies associated with novel algae or became rare or extinct themselves. Understanding long-term algal population dynamics is critical to forecast how algal lineage loss or, alternatively, an increase in algal diversity will impact coral resilience and survival.

Nitrate dynamics in coastal groundwater and rivers: Insights into oligotrophication management - Therese Line Laure Jokam Nenkam; Jing Zhang; Daisuke Komatsu; Keiji Horikawa; Ade S. Oktaviani (Groundwater for Sustainable Development, 2025)

Corrigendum to “Deck height did not affect behavioural measures of ‘natural movements’ and ‘adequate ventilation’ during 8 h and 23 h transport of weaner pigs” [Appl. Anim. Behav. Sci. 290 (2025) 106714] - Cecilie Kobek-Kjeldager; Line D. Jensen; Leslie Foldager; Marianne Kaiser; Karen Thodberg; Mette S. Herskin (Applied Animal Behaviour Science, 2025)

Optimal movement decisions in complex landscapes - Line S. Cordes; Charles M. Bishop; Luca Börger; Jacob Nabe-Nielsen; Stephanie M. Harris (Trends in Ecology & Evolution, 2025)

Balancing act: A participatory system dynamics approach for Mar Menor’s sustainable future - Mahla Rashidian; Valentina Elena Tartiu; Isabel Seifert-Dähnn; Maximilian Nawrath; Line Johanne Barkved; Pablo Blanco-Gómez; Marckbyn S. Rodríguez-Vélez (Ecological Modelling, 2025)

Deck height did not affect behavioural measures of ‘natural movements’ and ‘adequate ventilation’ during 8 h and 23 h transport of weaner pigs - Cecilie Kobek-Kjeldager; Line D. Jensen; Leslie Foldager; Marianne Kaiser; Karen Thodberg; Mette S. Herskin (Applied Animal Behaviour Science, 2025)

Toxic and essential elements in primary teeth and maternal blood during pregnancy: The Norwegian Mother, Father and Child Cohort Study (MoBa) and the MoBaTooth Biobank - Synnøve Stokke Jensen; Manish Arora; Christine Austin; Anne Lise Brantsæter; Line Småstuen Haug; Helle K. Knutsen; Stein Atle Lie; Kristin S. Klock (Environmental Research, 2025)

Evaluating environmental impacts of micro, mini and small hydropower plants in Norway - Richard D. Hedger; Mahmoud S. Kenawi; Line E. Sundt-Hansen; Tor Haakon Bakken; Brett K. Sandercock (Journal of Environmental Management, 2025)

Experimental study on temperature difference between the interior and exterior of the vehicle transporting weaner pigs - Guoxing Chen; Cecilie Kobek-Kjeldager; Line D. Jensen; Jens K. Kristensen; Marianne Kaiser; Karen Thodberg; Guoqiang Zhang; Li Rong; Mette S. Herskin; Leslie Foldager (Biosystems Engineering, 2024)

Fucoidans from Laminaria hyperborea demonstrate bactericidal activity against diverse bacteria - Michael L. C. Beagan; Line L Bang; Jens S. Pettersen; Rasmus B. Grønnemose; Sebastian Foertsch; Thomas E. Andersen; Ming Ding (Journal of Applied Phycology, 2024)
Fucoidans are a heterogenous class of fucose-rich sulfated carbohydrates which have attracted increasing attention in cancer and inflammation research due to their bioactive properties. There are reports that fucoidans may have direct antibacterial effects and synergy with antibiotics. However, the literature is conflicting, potentially due to the limited reporting of origin, characteristics, and extraction methods of the fucoidans tested. Here we report the results of 18 defined fucoidans screened for direct, indirect, and synergistic antibacterial effects. 15 distinct fucoidan fractions, isolated from Laminaria hyperborea using a solvent-free extraction process, were characterised for molecular weight, pH, viscosity, and sulfur content. These, together with three commercially available crude fractions, were assessed at concentrations from 0.03125-24 mg mL -1 for minimum inhibitory concentration against Staphylococcus aureus , Streptococcus mutans and Streptococcus sanguinis. Furthermore, we tested a selection of fucoidans for antibacterial synergy with vancomycin and indirect antibacterial effects in whole blood survival assays. Reverse-transcription quantitative polymerase chain reaction (RT-qPCR) was performed to assess the stress response in fucoidan-treated S. aureus cultures. We have identified one fucoidan fraction with bactericidal activity against diverse bacteria. This effect is dose-, fucoidan fraction- and bacteria-specific, and furthermore, not related to osmotic stress. No synergistic effects were observed with fucoidan in combination vancomycin. Fucoidans have exciting potential as antimicrobial agents. Further analysis is required to establish the precise molecular characteristics responsible for their potent bactericidal activity.

Managing the remediation strategy of contaminated megasites using field-scale calibration of geo-electrical imaging with chemical monitoring - Léa Lévy; Thue S. Bording; Gianluca Fiandaca; Anders Vest Christiansen; Line M. Madsen; Lars F. Bennedsen; Torben Højbjerg Jørgensen; Leah MacKinnon; Jørgen F. Christensen (Science of The Total Environment, 2024)

Validation of behavioural sampling techniques for 20-25 kg pigs during transport - Cecilie Kobek-Kjeldager; Line D. Jensen; Leslie Foldager; Marianne Kaiser; Karen Thodberg; Mette S. Herskin (Livestock Science, 2024)

Behaviour of cull sows during transport to slaughter – Effects of journey duration, a stationary period and temperature - Cecilie Kobek-Kjeldager; Line D. Jensen; Leslie Foldager; Louisa M. Gould; Karen Thodberg; Dorte Lene Schrøder-Petersen; Mette S. Herskin (Applied Animal Behaviour Science, 2024)

Effects of journey duration and temperature during pre-slaughter transport on behaviour of cull sows in lairage - Cecilie Kobek-Kjeldager; Line D. Jensen; Leslie Foldager; Karen Thodberg; Dorte L. Schrøder-Petersen; Mette S. Herskin (Research in Veterinary Science, 2023)

Current exposure to phthalates and DINCH in European children and adolescents – Results from the HBM4EU Aligned Studies 2014 to 2021 - Nina Vogel; Phillipp Schmidt; Rosa Lange; Antje Gerofke; Amrit K. Sakhi; Line S. Haug; Tina Kold Jensen; Hanne Frederiksen; Tamás Szigeti; Zsófia Csákó; Lubica Palkovicova Murinova; Miroslava Sidlovska; et al. (International Journal of Hygiene and Environmental Health, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Changes in perfluoroalkyl substances (PFAS) concentrations in human milk over the course of lactation: A study in Ronneby mother-child cohort - Annelise J. Blomberg; Line S. Haug; Christian Lindh; Azemira Sabaredzovic; Daniela Pineda; Kristina Jakobsson; Christel Nielsen (Environmental Research, 2023)

Hippocampal neurochemicals are associated with exercise group and intensity, psychological health, and general cognition in older adults - Line S. Reitlo; Jelena M. Mihailovic; Dorthe Stensvold; Ulrik Wisløff; Fahmeed Hyder; Asta Kristine Håberg (GeroScience, 2023)
Based on the premise that physical activity/exercise impacts hippocampal structure and function, we investigated if hippocampal metabolites for neuronal viability and cell membrane density (i.e., N-acetyl aspartate (NAA), choline (Cho), creatine (Cr)) were higher in older adults performing supervised exercise compared to following national physical activity guidelines. Sixty-three participants (75.3 ± 1.9 years after 3 years of intervention) recruited from the Generation 100 study (NCT01666340_date:08.16.2012) were randomized into a supervised exercise group (SEG) performing twice weekly moderate- to high-intensity training, and a control group (CG) following national physical activity guidelines of ≥ 30-min moderate physical activity ≥ 5 days/week. Hippocampal body and head volumes and NAA, Cho, and Cr levels were acquired at 3T with magnetic resonance imaging and spectroscopic imaging. Sociodemographic data, peak oxygen uptake (VO 2peak ), exercise characteristics, psychological health, and cognition were recorded. General linear models were used to assess group differences and associations corrected for age, sex, education, and hippocampal volume. Both groups adhered to their training, where SEG trained at higher intensity. SEG had significantly lower NAA/Cr in hippocampal body than CG ( p = 0.04). Across participants, higher training intensity was associated with lower Cho/Cr in hippocampal body ( p < 0.001). Change in VO 2peak , increasing VO 2peak from baseline to 3 years, or VO 2peak at 3 years were not associated with hippocampal neurochemicals. Lower NAA/Cr in hippocampal body was associated with poorer psychological health and slightly higher cognitive scores. Thus, following the national physical activity guidelines and not training at the highest intensity level were associated with the best neurochemical profile in the hippocampus at 3 years.

Cross-sectional associations between exposure to per- and polyfluoroalkyl substances and body mass index among European teenagers in the HBM4EU aligned studies - Tessa Schillemans; Nina Iszatt; Sylvie Remy; Greet Schoeters; Mariana F. Fernández; Shereen Cynthia D'Cruz; Anteneh Desalegn; Line S. Haug; Sanna Lignell; Anna Karin Lindroos; Lucia Fábelová; Lubica Palkovicova Murinova; et al. (Environmental Pollution, 2023)

The effects of marine heatwaves on acute heat tolerance in corals - Magena R. Marzonie; Line K. Bay; David G. Bourne; Andrew S. Hoey; Samuel Matthews; Josephine J. V. Nielsen; Hugo B. Harrison (Global Change Biology, 2023)
Scleractinian coral populations are increasingly exposed to conditions above their upper thermal limits due to marine heatwaves, contributing to global declines of coral reef ecosystem health. However, historic mass bleaching events indicate there is considerable inter‐ and intra‐specific variation in thermal tolerance whereby species, individual coral colonies and populations show differential susceptibility to exposure to elevated temperatures. Despite this, we lack a clear understanding of how heat tolerance varies across large contemporary and historical environmental gradients, or the selective pressures that underpin this variation. Here we conducted standardised acute heat stress experiments to identify variation in heat tolerance among species and isolated reefs spanning a large environmental gradient across the Coral Sea Marine Park. We quantified the photochemical yield ( F v /F m ) of coral samples in three coral species, Acropora cf humilis , Pocillopora meandrina , and Pocillopora verrucosa , following exposure to four temperature treatments (local ambient temperatures, and + 3°C, +6°C and + 9°C above local maximum monthly mean). We quantified the temperature at which F v /F m decreased by 50% (termed ED50) and used derived values to directly compare acute heat tolerance across reefs and species. The ED50 for Acropora was 0.4–0.7°C lower than either Pocillopora species, with a 0.3°C difference between the two Pocillopora species. We also recorded 0.9°C to 1.9°C phenotypic variation in heat tolerance among reefs within species, indicating spatial heterogeneity in heat tolerance across broad environmental gradients. Acute heat tolerance had a strong positive relationship to mild heatwave exposure over the past 35 years (since 1986) but was negatively related to recent severe heatwaves (2016–2020). Phenotypic variation associated with mild thermal history in local environments provides supportive evidence that marine heatwaves are selecting for tolerant individuals and populations; however, this adaptive potential may be compromised by the exposure to recent severe heatwaves.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Bioactive Scaffolds in Stem Cell-Based Therapies for Myocardial Infarction: a Systematic Review and Meta-Analysis of Preclinical Trials - Kashif Khan; Karina Gasbarrino; Ibtisam Mahmoud; Line Dufresne; Stella S. Daskalopoulou; Adel Schwertani; Renzo Cecere (Stem Cell Reviews and Reports, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Environment rather than provenance explains levels of foliar phenolics in European beech (Fagus sylvatica L.) seedlings - Johanna S. Steen; Johan Asplund; Marit H. Lie; Line Nybakken (Trees, 2021)
With progressive climate change, the chemical defense in European beech ( Fagus sylvatica L.) is likely to change, which might impact its fitness and ability to establish beyond its current northern distribution limit. We studied the phenolic defense in six beech provenances grown in three common gardens in Norway the two first years after planting. We analyzed low molecular weight phenolic compounds by HPLC and condensed tannins by the acid-butanol assay. Sampling year explained most of the variance in phenolic defense, followed by environment (growing location), while the genetic background (provenance) showed the least explanatory power. After the first year in the field, the northernmost growing location had about 70% higher concentration of low molecular weight phenolics than the southern growing locations. The concentrations of condensed tannins, however, were lowest in the north. The mean concentration of total low molecular weight phenolics was twice as high after the first year compared to the second year. After the second year, the differences between the growing locations in many cases disappeared. The differences between the growing locations are probably caused by differences in temperature and soil fertility, while we attribute the decrease in low molecular weight phenols from the first to the second year to decreased water and nutrient stress, as well as aging. Our results suggest that intraspecific variations in concentration and composition of phenolic compounds in beech are caused by differences in the environment to a greater extent than the genetic background, which may indicate fast changes in chemical defense with climate change.

Second-tier trio exome sequencing after negative solo clinical exome sequencing: an efficient strategy to increase diagnostic yield and decipher molecular bases in undiagnosed developmental disorders - Frederic Tran Mau-Them; Sebastien Moutton; Caroline Racine; Antonio Vitobello; Ange-Line Bruel; Sophie Nambot; Steven A. Kushner; Femke M. S. de Vrij; Daphné Lehalle; Nolwenn Jean-Marçais; François Lecoquierre; Julian Delanne; et al. (Human Genetics, 2020)

Symbiont community diversity is more variable in corals that respond poorly to stress - Lauren I. Howe‐Kerr; Benedicte Bachelot; Rachel M. Wright; Carly D. Kenkel; Line K. Bay; Adrienne M. S. Correa (Global Change Biology, 2020)
Coral reefs are declining globally as climate change and local water quality press environmental conditions beyond the physiological tolerances of holobionts—the collective of the host and its microbial symbionts. To assess the relationship between symbiont composition and holobiont stress tolerance, community diversity metrics were quantified for dinoflagellate endosymbionts (Family: Symbiodiniaceae) from eight Acropora millepora genets that thrived under or responded poorly to various stressors. These eight selected genets represent the upper and lower tails of the response distribution of 40 coral genets that were exposed to four stress treatments (and control conditions) in a 10‐day experiment. Specifically, four ‘best performer’ coral genets were analyzed at the end of the experiment because they survived high temperature, high p CO 2 , bacterial exposure, or combined stressors, whereas four ‘worst performer’ genets were characterized because they experienced substantial mortality under these stressors. At the end of the experiment, seven of eight coral genets mainly hosted Cladocopium symbionts, whereas the eighth genet was dominated by both Cladocopium and Durusdinium symbionts. Symbiodiniaceae alpha and beta diversity were higher in worst performing genets than in best performing genets. Symbiont communities in worst performers also differed more after stress exposure relative to their controls (based on normalized proportional differences in beta diversity), than did best performers. A generalized joint attribute model estimated the influence of host genet and treatment on Symbiodiniaceae community composition and identified strong associations among particular symbionts and host genet performance, as well as weaker associations with treatment. Although dominant symbiont physiology and function contribute to host performance, these findings emphasize the importance of symbiont community diversity and stochasticity as components of host performance. Our findings also suggest that symbiont community diversity metrics may function as indicators of resilience and have potential applications in diverse disciplines from climate change adaptation to agriculture and medicine.

Temporal and spatial variation in fatty acid composition in Acropora tenuis corals along water quality gradients on the Great Barrier Reef, Australia - Melissa M. Rocker; David S. Francis; Katharina E. Fabricius; Bette L. Willis; Line K. Bay (Coral Reefs, 2019)

Preparation and Characterization of an Oral Vaccine Formulation Using Electrosprayed Chitosan Microparticles - Jorge Alberto S. Moreno; Danai-Anastasia Panou; Karen Stephansen; Ioannis S. Chronakis; Anja Boisen; Ana C. Mendes; Line Hagner Nielsen (AAPS PharmSciTech, 2018)

Use of non-antiretroviral drugs among individuals with and without HIV-infection: a Danish nationwide study - Line D. Rasmussen; Gitte Kronborg; Carsten S. Larsen; Court Pedersen; Jan Gerstoft; Niels Obel; Anton Pottegård (Infectious Diseases, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Does genetic distance between parental species influence outcomes of hybridization among coral reef butterflyfishes? - Stefano R. Montanari; Jean‐Paul A. Hobbs; Morgan S. Pratchett; Line K. Bay; Lynne Van Herwerden (Molecular Ecology, 2014)
Christmas Island is located at the overlap of the Indian and Pacific Ocean marine provinces and is a hot spot for marine hybridization. Here, we evaluate the ecological framework and genetic consequences of hybridization between butterflyfishes Chaetodon guttatissimus and Chaetodon punctatofasciatus . Further, we compare our current findings to those from a previous study of hybridization between Chaetodon trifasciatus and Chaetodon lunulatus . For both species groups, habitat and dietary overlap between parental species facilitate frequent heterospecific encounters. Low abundance of potential mates promotes heterospecific pair formation and the breakdown of assortative mating. Despite similarities in ecological frameworks, the population genetic signatures of hybridization differ between the species groups. Mitochondrial and nuclear data from C. guttatissimus × C. punctatofasciatus (1% divergence at cyt b ) show bidirectional maternal contributions and relatively high levels of introgression, both inside and outside the Christmas Island hybrid zone. In contrast, C. trifasciatus × C. lunulatus (5% cyt b divergence) exhibit unidirectional mitochondrial inheritance and almost no introgression. Back‐crossing of hybrid C. guttatissimus × C. punctatofasciatus and parental genotypes may eventually confound species‐specific signals within the hybrid zone. In contrast, hybrids of C. trifasciatus and C. lunulatus may coexist with and remain genetically distinct from the parents. Our results, and comparisons with hybridization studies in other reef fish families, indicate that genetic distance between hybridizing species may be a factor influencing outcomes of hybridization in reef fish, which is consistent with predictions from terrestrially derived hybridization theory.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Characterization and reactivity of broiler chicken sera to selected recombinant Campylobacter jejuni chemotactic proteins - Hung-Yueh Yeh; Kelli L. Hiett; John E. Line; Bruce S. Seal (Archives of Microbiology, 2014)

Mark‐recapture modeling accounting for state uncertainty provides concurrent estimates of survival and fecundity in a protected harbor seal population - Line S. Cordes; Paul M. Thompson (Marine Mammal Science, 2014)
Harbor seal breeding behavior and habitats constrain opportunities for individual‐based studies, and no current estimates of both survival and fecundity exist for any of the populations studied worldwide. As a result, the drivers underlying the variable trends in abundance exhibited by harbor seal populations around the world remain uncertain. We developed an individual‐based study of harbor seals in northeast Scotland, whereby data were collected during daily photo‐identification surveys throughout the pupping seasons between 2006 and 2011. However, a consequence of observing seals remotely meant that information on sex, maturity‐stage, or breeding status was not always available. To provide unbiased estimates of survival rates we conditioned initial release of individuals on the first time sex was known to estimate sex‐specific survival rates, while a robust design multistate model accounting for uncertainty in breeding status was used to estimate reproductive rate of multiparous and ≥3‐yr‐old females. Survival rates were estimated at 0.95 (95% CI = 0.91–0.97) for females and 0.92 (0.83–0.96) for males, while reproductive rate was estimated at 0.89 (0.75–0.95) for multiparous and 0.69 (0.64–0.74) for ≥3‐yr‐old females. Stage‐based population modeling indicated that this population should be recovering, even under the current shooting quotas implemented by the recent management plan.

Using Changes in Agricultural Utility to Quantify Future Climate‐Induced Risk to Conservation - LYNDON D. ESTES; LYDIE‐LINE PAROZ; BETHANY A. BRADLEY; JONATHAN M.H. GREEN; DAVID G. HOLE; STEPHEN HOLNESS; GUY ZIV; MICHAEL G. OPPENHEIMER; DAVID S. WILCOVE (Conservation Biology, 2014)
Much of the biodiversity‐related climate change impacts research has focused on the direct effects to species and ecosystems. Far less attention has been paid to the potential ecological consequences of human efforts to address the effects of climate change, which may equal or exceed the direct effects of climate change on biodiversity. One of the most significant human responses is likely to be mediated through changes in the agricultural utility of land. As farmers adapt their practices to changing climates, they may increase pressure on some areas that are important to conserve (conservation lands) whereas lessening it on others. We quantified how the agricultural utility of South African conservation lands may be altered by climate change. We assumed that the probability of an area being farmed is linked to the economic benefits of doing so, using land productivity values to represent production benefit and topographic ruggedness as a proxy for costs associated with mechanical workability. We computed current and future values of maize and wheat production in key conservation lands using the DSSAT4.5 model and 36 crop‐climate response scenarios. Most conservation lands had, and were predicted to continue to have, low agricultural utility because of their location in rugged terrain. However, several areas were predicted to maintain or gain high agricultural utility and may therefore be at risk of near‐term or future conversion to cropland. Conversely, some areas were predicted to decrease in agricultural utility and may therefore prove easier to protect from conversion. Our study provides an approximate but readily transferable method for incorporating potential human responses to climate change into conservation planning. Uso de Cambios en la Utilidad Agrícola para Cuantificar Riesgos Futuros para la Conservación Inducidos por el Clima

Isolation and characterization of twenty microsatellite markers for the study of hybridization in butterflyfish of the genus Chaetodon - Stefano R. Montanari; Michael G. Gardner; Jean-Paul A. Hobbs; Morgan S. Pratchett; Line K. Bay; Lynne van Herwerden (Conservation Genetics Resources, 2013)

Harp seal foraging behaviour during summer around Svalbard in the northern Barents Sea: diet composition and the selection of prey - Ulf Lindstrøm; Kjell T. Nilssen; Line M. S. Pettersen; Tore Haug (Polar Biology, 2013)

Comparing survey methods for monitoring vegetation change through time in a restored peatland - Line Rochefort; F. Isselin-Nondedeu; S. Boudreau; M. Poulin (Wetlands Ecology and Management, 2013)

Corrigendum - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON MCNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S. A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)

Combining management and breeding advances to improve field pea (Pisum sativum L.) grain yields under changing climatic conditions in south-eastern Australia - L. S. McMurray; J. A. Davidson; M. D. Lines; A. Leonforte; M. U. Salam (Euphytica, 2011)

Searching for small σB-regulated genes in Staphylococcus aureus - Jesper S. Nielsen; Mie H. G. Christiansen; Mette Bonde; Sanne Gottschalk; Dorte Frees; Line E. Thomsen; Birgitte H. Kallipolitis (Archives of Microbiology, 2011)

Isolation and characterization of 29 microsatellite loci for studies of population connectivity in the butterflyfishes Chaetodon trifascialis and Chaetodon lunulatus - Rebecca J. Lawton; Morgan S. Pratchett; Line K. Bay (Conservation Genetics Resources, 2010)

The skin as a social organ - India Morrison; Line S. Löken; Håkan Olausson (Experimental Brain Research, 2010)

Mice overexpressing the 5-hydroxytryptamine transporter show no alterations in feeding behaviour and increased non-feeding responses to fenfluramine - A. Pringle; K. A. Jennings; S. Line; D. M. Bannerman; S. Higgs; T. Sharp (Psychopharmacology, 2008)

Modeling and simulation of adherence: Approaches and applications in therapeutics - Leslie A. Kenna; Line Labbé; Jeffrey S. Barrett; Marc Pfister (The AAPS Journal, 2005)

Worker policing persists in a hopelessly queenless honey bee colony ( Apis mellifera ) - N. Chline; S. J. Martin; F. L. W. Ratnieks (Insectes Sociaux, 2004)

Field experiment ofSphagnum reintroduction on a dry abandoned peatland in eastern Canada - Jean-Luc Bugnon; Line Rochefort; Jonathan S. Price (Wetlands, 1997)